Optimal echo time for functional MRI of the infant brain identified in response to noxious stimulation. Issue 2 (21st September 2016) - Goksan, Sezgi; Hartley, Caroline; Hurley, Samuel A.; Winkler, Anderson M.; Duff, Eugene P.; Jenkinson, Mark; Rogers, Richard; Clare, Stuart; Slater, Rebeccah
Abstract : Purpose: Blood oxygen level dependent (BOLD) brain activity, measured using functional MRI (fMRI), is dependent on the echo time (TE) and the reversible spin–spin relaxation time constant ( T 2 * ) that describes the decay of transverse magnetization. Use of the optimal TE during fMRI experiments allows maximal sensitivity to BOLD to be achieved. Reports that T 2 * values are longer in infants (due to higher water concentrations and lower lipid content) have led to the use of longer TEs during infant fMRI experiments; however, the optimal TE has not been established. Methods: In this study, acute experimental mildly noxious stimuli were applied to the heel in 12 term infants (mean gestational age = 40 weeks, mean postnatal age = 3 days); and the percentage change in BOLD activity was calculated across a range of TEs, from 30 to 70 ms, at 3 Tesla. In addition, T 2 * maps of the whole brain were collected in seven infants. Results: The maximal change in BOLD occurred at a TE of 52 ms, and the average T 2 * across the whole brain was 99 ms. Conclusion: A TE of approximately 50 ms is recommended for use in 3T fMRI investigations in term infants. Magn Reson Med 78:625–631, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine.